How to Survive in between Colonialism and Corporatism: A Critical Case Analysis of South Korean Academia - Hyu-Yong Park (Research Aspects in Arts and Social Studies Vol. 3, 2022)
Driven by the ideologies of neoliberalism and market capitalism, the higher education in South Korea has recently been operated and become more and more corporatized under the context of colonial academic dependency. Under this perspective, we discuss the academic dependency and corporatization of, especially, Korean colleges by pinpointing three prominent events: first, the recent attempt by Korean colleges to adopt the American journal accreditation system; second, the annexation of the universities to Chabeol to make universities more competitive and efficient; and third, Korean college policies for expanding English-mediated courses in their curricula. The theoretical framework of this paper is the criticism of neo-colonialism, neo-liberalism, and the critical theories. The real purposes of higher education, which shouldn’t be determined solely by the logic of competition and scientific achievement, are diminished by these changes, according to our argument, which makes them illegal and have a negative impact on the atmospheres of higher education and academia in Korea. Additionally, these modifications disrespect the freedom of thought, speech, and study in lecturers’ and students’ native languages. We offer alternate viewpoints and methods for the Korean academic community to reestablish their own academic autonomy and independence.